Bioadsorption by coffee leaves in poluted river Mantaro water at Central Peru - Vitor Ramos, Yanela Kimberly (2022)
The biosorption of heavy metals is the property of some types of biomass, a process that captures or accumulates metal ions, allowing their removal or immobilization. The present study was carried out in the Mantaro river, following the recommendations of the ANA (National Water Authority), the experimental process was carried out in the laboratories of the Universidad Continental and the Volcan Mining Company, for this purpose the drying of the coffee leaves of the species (Caturra-arabic coffea) and its subsequent grinding, then it was added in 4 different proportions for samples of 250 ml of water. The first results showed that the water contains lead (0.1 mg / l), copper (4.12 mg / l), iron (0.01 mg / l) and zinc (0.42 mg / l) with a pH (7.53) and electrical conductivity (671μS).which are not recommended according to the Environmental Quality Standards, after adding the coffee leaf allowing it to act in a period of 48 hours, the best result was with the second sample adsorbing lead (0%), copper (95.15%), iron (0%) and zinc (52.38%) with a pH of 7.05 and electrical conductivity (664μS). Coffee leaves were more effective in reducing copper by up to 95.15%.